Dual-energy perfusion-CT in recurrent pancreatic cancer: preliminary results = Dual-Energy Perfusions-CT bei Pankreaskarzinomrezidiven–Vorläufige Ergebnisse - Fritz, Franziska; Skornitzke, Stephan; Hackert, Thilo; Kauczor, Hans-Ulrich; Stiller, Wolfram; Grenacher, Lars; Klauß, Miriam (RöFo, 2016)
Purpose: To evaluate the diagnostic performance of dual energy (DE) perfusion-CT for the differentiation between postoperative soft-tissue formation and tumor recurrence in patients after potentially curative pancreatic cancer resection. Material and methods: 24 patients with postoperative soft-tissue formation in the conventional regular follow-up CT acquisition after pancreatic cancer resection with curative intent were included prospectively. They were examined with a 64-row dual-source CT using a dynamic sequence of 34 DE acquisitions every 1.5 s (80 ml of iodinated contrast material, 370 mg/ml, flow rate 5 ml/s). Weighted average (linearly blended M0.5) 120kVp-equivalent dual-energy perfusion image data sets were evaluated with a body-perfusion CT tool (see above) for estimating blood flow, permeability, and blood volume. Diagnosis was confirmed by histological study (n = 4) and by regular follow-up. Results: Final diagnosis was local recurrence of pancreatic cancer in 15 patients and unspecific postoperative tissue formation in 9 patients. The blood-flow values for recurrence tissue trended to be lower compared to postoperative tissue formation with 16.6 ml/100 ml/min and 24.7 ml/100 ml/min, respectively for weighted average 120kVp-equivalent image data, which was not significant (n.s.) (p = 0.06, significance level 0.05). Permeability- and blood-volume values were only slightly lower in recurrence tissue (n.s.). Conclusion: DE perfusion-CT is feasible in patients after pancreatic cancer resection and a promising functional imaging technique. As only a trend for lower perfusion values in local recurrence compared to unspecific postoperative alterations was found, the perfusion differences are not yet sufficient to differentiate between malignancy and unspecific postoperative alterations for this new technique. Further studies and technical improvements are needed to generate reliable data for this clinically highly relevant differentiation. Key points: • DE Perfusion CT is feasible in patients after pancreatic cancer resection. • While reliable differentiation of unspecific postoperative tissue formation from recurrent malignancy cannot be achieved yet, it is within reach. • DE Perfusion CT has the potential to overcome todays limitations of pure morphological diagnosis of recurrent pancreatic cancer. Citation Format: • Fritz F, Skornitzke S, Hackert T et al. Dual-Energy Perfusion-CT in Recurrent Pancreatic Cancer - Preliminary Results. Fortschr Röntgenstr 2016; 188: 559 - 565
Gesehen am 28.05.2020